2009
DOI: 10.1007/s00345-009-0406-0
|View full text |Cite
|
Sign up to set email alerts
|

Fertility potential after unilateral and bilateral orchidopexy for cryptorchidism

Abstract: Men who underwent bilateral orchidopexy in their childhood have appreciably poorer prognosis for fertility compared to men who underwent a unilateral procedure. Our study also confirmed that men who underwent unilateral orchidopexy in their childhood before the age of 8 years have better prognosis for fertility compared to those who were operated later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 31 publications
6
55
1
1
Order By: Relevance
“…This is of concern, as late orchidopexy may be associated with increased risk of testicular cancer and diminished fertility potential in boys. [22][23][24][25][26] Two recent systematic reviews reported a 2-to 32-fold increased risk of testicular cancer in men with a history of UDT, with the risk lower for younger age at orchidopexy but higher for previous bilateral UDT. 8,27 Such findings have prompted a significant reduction in the recommended age to perform orchidopexy in the past decades, to its current 12 months of age.…”
Section: Figurementioning
confidence: 99%
“…This is of concern, as late orchidopexy may be associated with increased risk of testicular cancer and diminished fertility potential in boys. [22][23][24][25][26] Two recent systematic reviews reported a 2-to 32-fold increased risk of testicular cancer in men with a history of UDT, with the risk lower for younger age at orchidopexy but higher for previous bilateral UDT. 8,27 Such findings have prompted a significant reduction in the recommended age to perform orchidopexy in the past decades, to its current 12 months of age.…”
Section: Figurementioning
confidence: 99%
“…Other studies of hormonal profiles have documented different levels of inhibin B, FSH and LH levels. Patients with bilateral undescended testes have significantly lower sperm concentration and inhibin B levels, while showing higher FSH and LH levels than those with unilateral undescended testis [23].…”
Section: Discussionmentioning
confidence: 87%
“…This has been confirmed by studies showing improvement of both testicular volume and sperm count in children operated before two years of age [1]- [3]. Patients who underwent treatment for bilateral undescended testis have a reduced fertility potential when compared to patients with unilateral orchiopexy, as confirmed by Trsinar and Muravec [4]. Another clinical problem linked to cryptorchidism is the incidence of testicular tumors, considered to be 5 to 10 times higher than in the general population [5].…”
Section: Introductionmentioning
confidence: 72%